The Financial Crisis and the Global South A Development Perspective - Akyüz, Yilmaz (Pluto Press, 2013)
This book is a major contribution exploring the policy options available for developing and emerging economies in response to the global economic crises.Written by a highly respected development economist, the book gives a clear-eyed account of the issues particular to these countries and critically evaluates different policy approaches, including reforms in financial, monetary and trade policies. Informed by deep scholarship as well as practical experience, Yilmaz Akyuz draws on empirical data, historical context and theoretical expertise, with special attention paid to issues such as the role of the International Monetary Fund and China.The Financial Crisis and the Global South is a landmark book that will be of interest to practitioners, scholars, theorists and students of economics and development studies.